1993
DOI: 10.1002/j.2161-1920.1993.tb00960.x
|View full text |Cite
|
Sign up to set email alerts
|

The Timing of Counselor Contact in the Use of a Computer Information Delivery System With Adult Career Counseling Clients

Abstract: Treatment outcome differences based on the timing of counselor contact in the use of a computer information delivery system were investigated. The results indicate significant differences between scores for the postintervention counseling and control groups on the Career Decision Scale. Results also indicate significant differences between the postintervention and en-route counseling groups for scores on the Computer Liking subscale of the Computer Attitude Scale. Implications are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

1994
1994
2005
2005

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 11 publications
1
5
0
Order By: Relevance
“…That is to say, both treatment groups experienced decreased levels of career indecision, but neither group significantly outperformed the other on this measure. These findings echoed previous studies that confirmed that comprehensive programs and shorter term interventions can be effective in reducing career indecision and increasing career certainty (Cairo, 1983;Cooper, 1986;Fukuyama et al, 1988;Harris et al, 1985;Mawson & Kahn, 1993;McAuliffe & Fredrickson, 1990;Niles, 1993;Oliver & Spokane, 1988;Peterson et al, 1991;Rayman et al, 1983;Savickas, 1990). Nonetheless, this study was unique in that it compared the number of levels of treatment parameters that were integrated into the two conditions.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…That is to say, both treatment groups experienced decreased levels of career indecision, but neither group significantly outperformed the other on this measure. These findings echoed previous studies that confirmed that comprehensive programs and shorter term interventions can be effective in reducing career indecision and increasing career certainty (Cairo, 1983;Cooper, 1986;Fukuyama et al, 1988;Harris et al, 1985;Mawson & Kahn, 1993;McAuliffe & Fredrickson, 1990;Niles, 1993;Oliver & Spokane, 1988;Peterson et al, 1991;Rayman et al, 1983;Savickas, 1990). Nonetheless, this study was unique in that it compared the number of levels of treatment parameters that were integrated into the two conditions.…”
Section: Discussionsupporting
confidence: 87%
“…First, the interventions included the positive components of each treatment parameter. For example, occupational information was gained through computer and written means (Jepsen, 1972;Johnson et al, 1975), and computer interventions were followed by a meeting with a counselor (Niles, 1993). Second, career counseling theories (i. e., Me span, trait and factor, career decision making, and noncounsehg uses of career development theory) were used in combination following guidelines outlined by Sharf(1997).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of a computer as an adjunct to counseling is more effective when a counselor remains an active part of the overall intervention (Marin & Splete, 1991). Additionally, at what point a counselor participates in the process is important (Niles, 1993). Just as investigators have sought to find which clients respond best to bibliotherapy (Marrs, 1995), so too must career counselors undertake studies to ascertain how and with whom the Internet should be used.…”
Section: Benefits Limitations and Ethicsmentioning
confidence: 98%
“…Numerous studies have examined the use of computer programs and applications (Marin & Splete, 1991), interventions and processes (Barnes & Herr, 1998;Gati, Shenhav, & Givon, 1993). Other studies evaluated the timing of counselor contact with computers in career guidance and counseling (Niles, 1993), and others looked at whether or not the method was cost-effective (Whiston, Sexton, & Lasoff, 1998). Recently, the literature relating to career counseling and computers has focused on the Internet.…”
mentioning
confidence: 99%